2008
DOI: 10.1007/s11192-007-1935-1
|View full text |Cite
|
Sign up to set email alerts
|

Bibliographic coupling, common abstract stems and clustering: A comparison of two document-document similarity approaches in the context of science mapping

Abstract: This paper deals with two document-document similarity approaches in the context of science mapping: bibliographic coupling and a text approach based on the number of common abstract stems. We used 43 articles, published in the journal Information Retrieval, as test articles. An information retrieval expert performed a classification of these articles. We used the cosine measure for normalization, and the complete linkage method was used for clustering the articles. A number of articles pairs were ranked (1) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
29
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 13 publications
1
29
0
Order By: Relevance
“…A significant portion of bibliometric analysis has been focused on citation analysis, which traces through citations and reveals the intellectual structure from a macro perspective. The representatives are direct citation (Garfield 2004), journal co-citation analysis (Hu et al 2011;Mustafee et al 2014), document co-citation analysis (Li et al 2010;Gao et al 2012), document bibliographic coupling (Ahlgren and Jarneving 2008), author co-citation analysis (ACA) (White and Griffith 1981;Chen and Lien 2011), and author bibliographic coupling (Zhao and Strotmann 2008a;Ma 2012). Another important branch of bibliometric analysis is content analysis, which relies on natural language processing to analyze large corpora of literature text and depicts the intellectual structure from a micro perspective.…”
Section: Introductionmentioning
confidence: 99%
“…A significant portion of bibliometric analysis has been focused on citation analysis, which traces through citations and reveals the intellectual structure from a macro perspective. The representatives are direct citation (Garfield 2004), journal co-citation analysis (Hu et al 2011;Mustafee et al 2014), document co-citation analysis (Li et al 2010;Gao et al 2012), document bibliographic coupling (Ahlgren and Jarneving 2008), author co-citation analysis (ACA) (White and Griffith 1981;Chen and Lien 2011), and author bibliographic coupling (Zhao and Strotmann 2008a;Ma 2012). Another important branch of bibliometric analysis is content analysis, which relies on natural language processing to analyze large corpora of literature text and depicts the intellectual structure from a micro perspective.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, where the research reported in an earlier article (Ahlgren & Jarneving, 2008) is developed, we compare experimentally five approaches to document-document similarity in the context of science mapping. We compare (1) text-based approaches, (2) the citation-based bibliographic coupling approach, and (3) approaches that combine text-based approaches and bibliographic coupling.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of bibliographic coupling was introduced by Kessler (1963) who demonstrated the existence of the phenomenon and argued for its usefulness as an indicator of subject relatedness. However, as noted by Glänzel and Czerwon (1996) and De Bellis (2009) the technique lived a relatively quiet life until the 1990s when bibliometricians began to employ it for identifying and mapping clusters of subject-related documents (e.g., Ahlgren & Jarneving, 2008;Glänzel & Czerwon, 1996;Jarneving, 2007). As noted above, we believe that the bibliographic coupling technique has another promising potential -namely as a measure of the level of consensus in science.…”
Section: Introductionmentioning
confidence: 76%